Short-term inflation forecasting models for Nigeria - Sani I. Doguwa; Sarah O. Alade (CBN Journal of Applied Statistics, 2013)
Short-term inflation forecasting is an essential component of the monetary policy projections at the Central Bank of Nigeria. This paper proposes four short-term headline inflation forecasting models using the SARIMA and SARIMAX processes and compares their performance using the pseudo-out-of-sample forecasting procedure over July 2011 to September 2013. According to the results the best forecasting performance is demonstrated by the model based on the all items CPI estimated using the SARIMAX model. This model is, therefore, recommended for use in short-term forecasting of headline inflation in Nigeria. The forecasting performance up to eight months ahead, of the models based on the weighted sum of all items CPI components is relatively bad. For forecast of food inflation up to ten months ahead SARIMA is recommended, but for eleven to twelve months ahead the SARIMAX model performs better. However, the SARIMA model for core inflation consistently outperforms the SARIMAX model and should therefore be used to forecast core inflation.
Keywords: C22; E17; E31; 330; Consumer Price Index; SARIMA Process; SARIMAX Process; Statistical Loss Function; Forecast Evaluation